Effects of trade facilitation on trade costs in developed and developing countries: PPML analysis - Alaamshani, Imad Kareem; Hamzah, Hanny Zurina; Kaliappan, Shivee Ranjanee; Ismail, Normaz Wana (University of Malaya, 2021)
Trade facilitation reduces trade costs and eases the movement of goods and services. Studies have shown that trade flows increased by improving the trade facilitation process and reducing trade costs. The study aims to estimate the effects of trade facilitation enhancement on trade costs in 111 developed and developing countries over the 2008 to 2014 period using the Poisson-Pseudo Maximum Likelihood (PPML) estimator. The findings show that trade facilitation components such as border administration, business environment and transport and communication infrastructure reduce trade costs. This trade facilitation should have helped alleviate the effects of the financial recession and eased world trade recovery. On the other hand, the study finds that additional market access increases trade costs. The most important finding is that the effectiveness of trade facilitation is higher when more countries engage in trade and when those countries are together participating in trade facilitation.